2005
DOI: 10.3368/le.81.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Living with Hogs in Iowa: The Impact of Livestock Facilities on Rural Residential Property Values

Abstract: To better understand the magnitude of the effects of livestock feeding operations on residential property values, we constructed a new dataset that merges data on home sales with data on the location and size of livestock feeding operations in five rural counties of Iowa. We estimated a hedonic model to explain variations in residential sales price with standard house attributes, such as number of bedrooms and square feet of living space, as well as the effects of distance and density of livestock feeding oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 17 publications
2
50
0
1
Order By: Relevance
“…This choice is driven by practical reasons, since many housing characteristics are discrete variables and our empirical objective is to measure the impact of environmental factors on residential housing prices by focusing on 1 See Bontemps et al (2006) for an extensive list of references. 2 In studies analyzing this problem, impacts of agricultural pollution (e.g., intensive livestock operations) on house prices are measured using a proximity index reflecting the distance between residential houses and the sites of agricultural pollution (Palmquist et al, 1997;Herriges et al, 2005;Ready and Abdalla, 2005). As explained further in Section 4, this approach cannot be adopted owing to the lack of relevant information on the localization of house sales and the sources of agricultural pollution.…”
Section: Introductionmentioning
confidence: 99%
“…This choice is driven by practical reasons, since many housing characteristics are discrete variables and our empirical objective is to measure the impact of environmental factors on residential housing prices by focusing on 1 See Bontemps et al (2006) for an extensive list of references. 2 In studies analyzing this problem, impacts of agricultural pollution (e.g., intensive livestock operations) on house prices are measured using a proximity index reflecting the distance between residential houses and the sites of agricultural pollution (Palmquist et al, 1997;Herriges et al, 2005;Ready and Abdalla, 2005). As explained further in Section 4, this approach cannot be adopted owing to the lack of relevant information on the localization of house sales and the sources of agricultural pollution.…”
Section: Introductionmentioning
confidence: 99%
“…7(p59) Studies have also shown that property values can decline substantially when residences are near a CAFO. [63][64][65] According to an article in the journal of the Appraisal Institute, an international association of professional real estate appraisers, case studies demonstrate that "diminished marketability, loss of use and enjoyment, and loss of exclusivity can result in a diminishment ranging from 50% to nearly 90% of otherwise unimpaired value." 63(p306) Researchers in Pennsylvania have found that neighboring house prices decrease once the total live weight of confined animals exceeds 200 000 pounds.…”
Section: Family and Community Health/january-march 2010mentioning
confidence: 99%
“…All of these found that, when compared to residential, commercial or industrial uses, open space located within a given distance from a property has a positive impact on property price. Another series of studies found that house prices were negatively affected by animal production facilities within given distances (Abeles-Allison and Connor 1990; Palmquist et al 1997;Herriges et al 2005;Ready and Abdalla 2005). Several studies found that the observed effects depended on the distance between the individual house and the environmental effect examined (e.g.…”
Section: Spatial Distribution Of Public-good Benefitsmentioning
confidence: 99%